MORPHOLOGICAL VARIATIONS OF THE OSTIOMEATAL COMPLEX: ASSOCIATION BETWEEN THE SUPERIOR ATTACHMENT OF THE UNCINATE PROCESS AND OLFACTORY FOSSA DEPTH ON MULTIPLANAR CT (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe the distribution of the superior attachment of the uncinate process (SAUP) and olfactory fossa depth, and to assess whether these two key preoperative anatomical landmarks are associated or should be evaluated independently on multiplanar computed tomography (CT).Materials and Methods: A cross-sectional descriptive study was conducted on 136 nasal sides from 68 adult patients who underwent paranasal sinus CT at Gia Dinh People’s Hospital from June 2024 to June 2025. Consecutive eligible cases were enrolled using convenience sampling, without a pre-specified sample size calculation. CT images were assessed using a standardized review protocol by an experienced otorhinolaryngologist on the axial, coronal and sagittal planes. Olfactory fossa depth was classified according to Keros and the superior attachment of the uncinate process (SAUP) according to Landsberg and Friedman. Because each patient contributed two nasal sides, the primary analysis of the association between Keros classification and SAUP group was a patient-clustered generalized estimating equation (GEE) logistic regression; Fisher’s exact test on the detailed contingency table was used as a supplementary descriptive analysis.Results: Mean age was 47.2 ± 16.2 years; 58.8% of patients were female and 41.2% male. Keros type 2 was the most common pattern (75.0%), followed by type 1 (22.1%) and type 3 (2.9%). Uncinate attachment to the lamina papyracea (type 1) was observed in 57.4% of sides, while non-type-1 attachments accounted for 42.6%. Side-to-side asymmetry within the same patient was 14.7% for Keros classification, 52.9% for the 6-category Landsberg–Friedman SAUP, and 35.3% for the dichotomized SAUP (type 1 vs. types 2–6). The primary patient-clustered GEE analysis did not detect a statistically significant association between Keros classification and SAUP group (overall p = 0.222); Fisher’s exact test on the detailed contingency table was likewise non-significant (p = 0.307). Among Keros type 1 sides, 10/30 (33.3%) still had non-type-1 uncinate attachments.Conclusion: SAUP and olfactory fossa depth did not show a statistically significant association in this study. These findings suggest that the two structures should be evaluated independently on preoperative multiplanar CT, rather than inferring the safety of the skull base or the complexity of the frontal recess from a single anatomical landmark. Given the small number of Keros type 3 sides, the results should be interpreted with caution.
Keywords: Uncinate process, Olfactory fossa, Keros classification, Functional Endoscopic Sinus Surgery, Computed Tomography.